Cellular cholesterol efflux mediated by HDL isolated from subjects with low HDL levels and coronary artery disease - Uint,Luciana (2003)
OBJECTIVE: The aim of this study was to verify whether HDL particles isolated from patients with coronary artery disease (CAD) and low HDL-C had diminished ability to promote cholesterol efflux from cultured cells compared with HDL isolated from subjects without CAD and with normal HDL-C. METHODS: Smooth muscle cells isolated from human aortas cultured and radiolabeled with ³H-cholesterol were loaded with cholesterol and incubated with increasing concentrations of HDL isolated from 13 CAD patients with low HDL-C (CAD group) or from 5 controls without CAD (C group). Efflux of cellular cholesterol was measured by cellular depletion of radiolabeled cholesterol and by the appearance of ³H-cholesterol into experimental medium expressed as a percentage of total labeled cholesterol. RESULTS: Cholesterol efflux increased with the amount of HDL present in the medium, and no difference was found between groups at various HDL protein concentrations: efflux was 28 ± 6.3% (C) and 25.5 ± 8.9% (CAD) with 25 mg/mL; 34 ± 4.3% (C) and 31.9 ± 6.6% (CD) with 50 mg/mL and 39.5 ± 3.5% (C) and 37.1 ± 4.4% (CAD) with 100 mg/mL, HDL. CONCLUSION: Because the HDL fraction of CAD patients with low HDL-C have normal ability to extract cholesterol from cells of the vessel wall, it is suggested that low HDL-C atherogenicity should be ascribed to diminished concentrations of HDL particles rather than to the qualitative properties of the HDL fraction.